PSIXOLOGIYALÍQ IZERTLEWLERDE MUǴDARLÍQ ANALIZ XARAKTERISTIKASÍ - Saparov, Shıngıs Baxievich (SCIENCE and SOCIETY, 2026)
This article presents the concept, stages of development and significance of quantitative analysis in psychological research.